Role of Indian Government in Institutionalising CSR in India - Yadav, Karina (2013)
Despite contested origins and nature of CSR practises in India, namely the long-standing tradition versus nascent upheaval as well as philanthropic versus integrative stakeholder approach, today India stands at a new crossroad to redefine the social responsibilities of business. The Government of India plays hereby the leading role in transforming the CSR agenda of this emerging economic power. Consequently, the current paper looks at the role of Indian government in institutionalising CSR in India in light of recent public policy instruments.